QUESTIONS ON MAGUN AND THE EMERGING TRENDS IN HUMANITIES AND SOCIAL SCIENCES (ETHSS) - Ogunfeyimi, Adeleke (European Scientific Journal, ESJ, 2015)
African critical discourse is replete with existing studies on the concept of culture. Exploring several themes, most critics have focused on the significance of culture to the sustainable development and human capacity building in the Third World Nations. The theme of magun, however, has not received adequate critical attention even as a breathtaking phenomenon. Africa is a society in which extra-marital sex taboo is jealously secured and preserved. But, due to the growing western civilization and its influence on African cultures, many Africans have, in one way or the other, violated this precept thus compelling some men (husbands) to seek justice through various spiritual means to protect their wives. The most common one is casting the spell of magun on their wives. Magun is a mystical-sexual enchantment or embargo placed on a woman (usually by her husband) to check her infidelity(?) or as a deterrent to many (men) who otherwise could have been reckless(?) in their sexual life. If a woman is laced with magun, whoever (?) has sex with her will suffer certain terrible consequences such as death. Nonetheless, there are many questions on magun begging for answers: i. Does magun mean one should not climb a woman laced with magun during sexual contact because the word magun is simply translated as â€œdo not climbâ€? ii. Does it mean that one should not have sex with her at all irrespective of the style or method one wants to employ? iii. In these present days where lesbianism is the order of the day can a woman suffer magun by having sex with another that carries the magun spell? In other words, is magun gender-specific? iv. What role does technology (like the use of condom during sexual contact) play in the magun phenomenon? This paper attempts to provide answers to these and other related questions investigating and exploration magun in African and Christian religions as well as provide some Western medical explanations to it to demonstrate the significance of primitivism even in the face of western development.